A Survey on Dynamic Resource Allocation in Cognitive Radio Networks - Tamilarasan, S; Kumar, P (International Journal of Computer Sciences and Engineering, 2025)
In cognitive radio networks (CRN) an efficient spectrum allocation is a very big issues because of its lack of spectrum demand. Resources in CRN should be allocated based on dynamic access methods with respected to sensed radio atmosphere. A primary research challenge is that how should be allocated or assigned available unused spectrum to unlicensed users. The fitting portion of unmoving recurrence range existing together intellectual radios while amplifying all out transmission capacity utilization what's more, minimizing impedance is required for the productive range use in CRN. The technique for settled range portion came about to less range usage over the whole range. In this article we study the different fitting algorithms and present comprehensive analysis of each method used to improve the effective utilization of unused spectrum in CRN.